BARTLEBY: Stop optimising. Start pronking. (Economist, 2026)
The article explains the importance of optimisation and the human equivalents of pronking to addressing workplace inefficiency. It cites examples of pronking that include sending a quick text or email, or using an employee-engagement platform to send an industrialised message of appreciation, multitasking during remote meetings, and use of artificial intelligence (AI) tools to create a letter of recommendation and to screen employees during the recruitment process.